A study of prospective surveillance for inhibitors among persons with haemophilia in the United States. (22nd November 2013) - Soucie, J. M.; Miller, C. H.; Kelly, F. M.; Payne, A. B.; Creary, M.; Bockenstedt, P. L.; Kempton, C. L.; Manco‐Johnson, M. J.; Neff, A. T.; ,
Summary: Inhibitors are a rare but serious complication of treatment of patients with haemophilia. Phase III clinical trials enrol too few patients to adequately assess new product inhibitor risk. This project explores the feasibility of using a public health surveillance system to conduct national surveillance for inhibitors. Staff at 17 U.S. haemophilia treatment centres (HTC) enrolled patients with haemophilia A and B into this prospective study. HTC staff provided detailed historic data on product use and inhibitors at baseline, and postenrolment patients provided monthly detailed infusion logs. A central laboratory performed inhibitor tests on blood specimens that were collected at baseline, annually, prior to any planned product switch or when clinically indicated. The central laboratory also performed genotyping of all enrolled patients. From January 2006 through June 2012, 1163 patients were enrolled and followed up for 3329 person‐years. A total of 3048 inhibitor tests were performed and 23 new factor VIII inhibitors were identified, 61% of which were not clinically apparent. Infusion logs were submitted for 113 205 exposure days. Genotyping revealed 431 distinct mutations causing haemophilia, 151 of which had not previously been reported elsewhere in the world. This study provided critical information about the practical issues that must be addressed to successfully implement national inhibitor surveillance. Centralized testing with routine monitoring and confirmation of locally identified inhibitors will provide valid and representative data with which to evaluate inhibitor incidence and prevalence, monitor trends in occurrence rates and identify potential inhibitor outbreaks associated with products.